Analysis of Teacher Perceptions on Problem-Based Learning to Improve the Mathematical Abilities of Vocational High School Students - Muhamad Aris Sunandar; Farah Dzil Barr (Indonesian Journal of Educational Science (IJES), 2025)
This research aims to analyze the perceptions of vocational high school mathematics teachers towards Problem-Based Learning and evaluate the effectiveness of this method in improving students’ mathematical problem-solving abilities. This research is important because mathematical problem-solving skills are essential competencies that support students’ critical and creative thinking skills, yet they remain low in many schools. This research uses a mixed-method approach with a quantitative questionnaire to measure teachers’ perceptions of problem-based learning and qualitative interviews to explore more in-depth information. The participants were 45 vocational high school mathematics teachers in Kendal Regency who were selected using purposive sampling. Data were analyzed descriptively to identify patterns in teachers’ perceptions and to analyze interviews to understand the challenges of implementing the method. The results show that most teachers positively perceive problem-based learning, with 80% agreeing that this skill is essential. However, the main obstacles are the lack of teacher competence in innovative learning strategies and limited facilities. This research recommends continuous training for teachers and the development of problem-based modules to support the successful implementation of problem-based learning.